TOOLS TO FACILITATE ONLINE – DELIBERATION IN TERMS OF VIRTUALIZATION OF PUBLIC RELATIONS - Dziundziuk B.V. (Pressing Problems of Public Administration, 2016)
The factors that affect online deliberation are considered; the role of social media in online-deliberation is de ned; the aspects that affect online deliberation are analyzed.